Pattern of total organic carbon in sediments within the mangrove ecosystem - Li, Yue; Long, Chuqi; Dai, Zhijun; Zhou, Xiaoyan (Frontiers in Marine Science, 2024)
The sedimentary total organic carbon (TOC) in mangrove ecosystems plays an essential role in the global carbon storage. Nevertheless, little information is available about the pattern of TOC in sediments varying from bare and flat to those beneath mangroves. To find out the roles of new-developing mangroves in sedimentary TOC accumulation, a serials of sediment samples were collected from the creek mudflat zone (CMZ) through the fringe mangrove zone (FMZ) to the interior mangrove zone (IMZ) in young mangrove system of Nanliu River Delta in China. Sediment compositions, TOC, total nitrogen (TN), molar C/N ratios, and carbon stable isotopes (δ13C) were analyzed to examine the accumulation processes. The results revealed the distinct differences in the sedimentary TOC values, with an obvious increasing trend from the CMZ and FMZ to the IMZ. We quantified that terrestrials, marine-derived and mangrove-derived sources contributed 39.2-74.1%, 24.7-63.1% and 0.9-6.9%, respectively, to the sedimentary TOC in the mangrove ecosystems. The organic carbon accumulation rates ranged from 2.59 to 269.60 g•m-2•a-1, with values of 8.77 ± 19.87, 24.78 ± 12.53, 167.19 ± 57.79 g•m-2•a-1 for CMZ, FMZ and IMZ. Our work highlights information showing that young mangrove forests of the tropical delta have important potential for carbon storage.